Genetics of suspected thrombophilia in Serbian females with infertility, including three cases, homozygous for FII 20210A or FV 1691A mutations. (3rd April 2017) - Djurovic, Jelena; Stojkovic, Oliver; Todorovic, Jelena; Brajic, Aleksandra; Stankovic, Sanja; Obradovic, Svetlana; Stamenkovic, Gorana
Abstract: Reproductive failure (recurrent foetal loss, unexplained infertility and IVF implantation failure) may be, in a number of cases, explained by thrombophilia, either acquired or inherited. Several genes contribute to thrombophilia, some with major effect ( Factor V, Factor II ), and some with minor effect ( MTHFR, PAI-1, ATIII, etc.). The aim of this study was to estimate frequency of thrombophilia-associated genotypes ( FII 20210G > A, FV 1691G > A, MTHFR 677C > T and PAI-1 -675 4G/5G) in a group of 1631 Serbian women experiencing reproductive failure, and compare it with a healthy, female control group. Our results showed marginally significant ( p  = 0.050) differences in allele frequencies between patients and controls for the FV 1691 mutations. For the FII 20210G > A, although the statistical significance was not achieved ( p  = 0.076), we found higher frequency of variant allele in patients compared to controls (1.87% vs. 0.38%, respectively) which may point to a possible role of this polymorphism in thrombotic events. For the MTHFR 677C > T and PAI-1 -675 4G/5G, we found no difference in distributions of genotype or allele frequencies between these two groups ( p  > 0.05). For three subjects with very rare genotypes (two patients homozygous for FV 1691G > A and one patient homozygous for FII 20210G > A) we performed additional biochemical analyses for haemostasis, as well as genotyping of two polymorphisms ( MTHFR 1298A > C and ATIII 786G > A).